2014
DOI: 10.1177/0300985813519655
|View full text |Cite
|
Sign up to set email alerts
|

The Worm Turns

Abstract: A reductionist approach to the study of infection does not lend itself to an appraisal of the interactions that occur between 2 or more organisms that infect a host simultaneously. In reality, hosts are subject to multiple simultaneous influences from multiple pathogens along the spectrum from symbiotic microflora to virulent pathogen. In this review, we draw from our own work on Fasciola hepatica and that of others studying helminth co-infection to give examples of how such interactions can influence not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…As a cross-sectional study, the time sequence of infection remains unknown, and thus, observed nematode infections may have occurred before or after B. tribocorum infection. Immune modulation by nematodes via the downregulation of T helper type 1 immunity could alter immune responses to microparasites including Bartonella spp., thus impacting the acquisition and establishment of chronic persistent infections(Garza-Cuartero et al, 2014). Our results suggest that there may be effects across organ systems in rats that are co-infected with B. tribocorum and nematode parasites.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…As a cross-sectional study, the time sequence of infection remains unknown, and thus, observed nematode infections may have occurred before or after B. tribocorum infection. Immune modulation by nematodes via the downregulation of T helper type 1 immunity could alter immune responses to microparasites including Bartonella spp., thus impacting the acquisition and establishment of chronic persistent infections(Garza-Cuartero et al, 2014). Our results suggest that there may be effects across organ systems in rats that are co-infected with B. tribocorum and nematode parasites.…”
mentioning
confidence: 74%
“…Even microscopic lesions that suggest minor disease may substantially affect behaviour and immune responses through their cumulative effects (i.e., total disease burden; Snyder, Ward, & Treuting, 2016). Co-infections with >1 species of microparasite (i.e., viruses, bacteria and protozoa) and/or macroparasite (i.e., nematodes, cestodes, trematodes) may profoundly affect infectious disease epidemiology by creating more severe disease, immune system modulation and host behaviour modification, which may subsequently increase pathogen shedding and transmission (Bordes & Morand, 2011;Ezenwa, 2016;Ezenwa et al, 2016;Garza-Cuartero et al, 2014;Gibson et al, 2011;Raoul, Hegglin, & Giraudoux, 2015;Vaumourin, Vourc'h, Gasqui, & Vayssier-Taussat, 2015;Webster, 2001). Collectively, behaviour and immune responses to disease are a mechanism for how intrahost factors may influence pathogen transmission and persistence.…”
Section: Introductionmentioning
confidence: 99%
“…To date, vaccination trials with either purified native or recombinant F. hepatica proteins have reported a wide range of protection (30–89%) in ruminants151617. Interestingly, it has been proposed that induction of a robust Th1 response could protect the host not only from the infection1518 but also from bystander co-infections by down-regulating Th2 regulatory immunity19. Accordingly, protection induced by helminth vaccines has been associated with high IFN-γ and TNF production20.…”
mentioning
confidence: 99%
“…But in addition to these lesions, nematodes may also negatively affect rat health through their systemic influence on the immune system and response to microparasite infections (i.e., viruses, bacteria, and protozoa). 36 Other studies have identified a similarly diverse array of parasites in wild rats. 69,74 However, histopathology is required to detect the full array and distribution of parasites along with associated lesions (e.g., Eucoleus sp.…”
Section: Lesions Associated With Bacterial Infectionsmentioning
confidence: 98%